Developing craft skills with quasi-cases: The example of the Big Apple's flirtation with congestion pricing. (July 2015) - Straussman, Jeffrey D
This article adopts the perspective expounded by Weimer, and Vining and Weimer, that policy analysis requires "craft skills" and, therefore, one of the fundamental objectives of public affairs programs is to prepare graduates for the professional working world by providing opportunities to learn and practice these skills. Second, the article then introduces a method of experiential learning advanced by Weaver which he calls "quasi-cases." The two concepts are then linked through an exposition of a quasi-case—New York City's flirtation with "congestion pricing." The goal of the article is to show that by linking these two ideas, one can enhance experiential learning in the classroom (and outside the classroom) and thereby provide students with the opportunity to practice craft skills in semester length courses in addition to the usual approach of relying on internships and capstone projects to provide public affairs students with opportunities to learn what it means to be professional. The quasi-case of New York City's flirtation with congestion pricing illustrates the following ideas: 1) Economic concepts and tools are necessary but rarely sufficient to understand a policy issue adequately. 2) Policy takes place in a specific intergovernmental context that shapes both process and outcome. Understanding the intergovernmental context is important if one is to appreciate how various political constraints operate in the particular setting.